PENYULUHAN DAN PENDAMPINGAN MASYARAKAT DESA MERTAK DALAM PEMANFATAN LIMBAH TERNAK SAPI SEBAGAI PUPUK ORGANIK DAN PEMANFAATANYA PADA BUDIDAYA PERTANIAN - Enriansyah, Enriansyah; Fitriani, Anizah Nuryanti; Fitri, Alfira Wulan; Apriliani, Ravita Dwi; Nurul ‘ain, Nurul ‘ain; Hardiani, Eti; Triansyah, Muhammad; Santoso, Gunawan Hari; Nikmatullah, Aluh (Universitas Mataram, 2023)
One of the problems that exist in the Mertak Village community, especially Berami and Montong Gerantung hamlets, Pujut District, Central Lombok Regency, West Nusa Tenggara is the lack of public awareness of the utilization of livestock manure into organic fertilizer and its use in agricultural cultivation. This program aims to provide counseling and assistance to the people of Mertak Village to utilize livestock manure as organic fertilizer which has a sale value and can be used as a substitute for rare chemical fertilizers. The method we use is self-approach to the local community, after approaching the community we conduct training and assistance in making organic fertilizer from livestock manure, ending with socialization regarding the use of cow manure into organic fertilizer and its application in agricultural cultivation. The impact of this activity is 1) increasing public knowledge to process livestock manure into organic fertilizer. 2) creating public awareness to treat livestock manure 3) increasing community skills in making organic fertilizer from animal waste 4) growing public interest in utilizing organic fertilizer from livestock manure to agricultural